2005
DOI: 10.1029/2005wr004381
|View full text |Cite
|
Sign up to set email alerts
|

Coupled oceanic‐atmospheric variability and U.S. streamflow

Abstract: [1] A study of the influence of interdecadal, decadal, and interannual oceanicatmospheric influences on streamflow in the United States is presented. Unimpaired streamflow was identified for 639 stations in the United States for the period 1951-2002. The phases (cold/negative or warm/positive) of Pacific Ocean (El Niño-Southern Oscillation (ENSO) and Pacific Decadal Oscillation (PDO)) and Atlantic Ocean (Atlantic Multidecadal Oscillation (AMO) and North Atlantic Oscillation (NAO)) oceanicatmospheric influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
158
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(172 citation statements)
references
References 31 publications
10
158
3
1
Order By: Relevance
“…The NAO influences the tracks of TCs over the North Atlantic Ocean (Elsner and Kara 1999;Elsner and Kocher 2000;Keim et al 2004;Elsner et al 2006;Elsner and Jagger 2006;Dailey et al 2009). Additionally, there is evidence of reductions in winter precipitation in the southeastern United States during NAO2 phases (Stenseth et al 2002), although some studies indicate an insignificant relationship between the NAO and precipitation in the southeastern United States during other seasons (Stahle and Cleaveland 1992;Henderson and Vega 1996;Katz et al 2003;Tootle et al 2005;Hurrell and Deser 2009). Maxwell et al (2012) identified the NAO as the only significant variable affecting the likelihood of a TCDB impacting the southeast ACS during the period 1950-2008.…”
Section: A Interdecadal Tc Landfall and Tc Precipitation Variabilitymentioning
confidence: 99%
“…The NAO influences the tracks of TCs over the North Atlantic Ocean (Elsner and Kara 1999;Elsner and Kocher 2000;Keim et al 2004;Elsner et al 2006;Elsner and Jagger 2006;Dailey et al 2009). Additionally, there is evidence of reductions in winter precipitation in the southeastern United States during NAO2 phases (Stenseth et al 2002), although some studies indicate an insignificant relationship between the NAO and precipitation in the southeastern United States during other seasons (Stahle and Cleaveland 1992;Henderson and Vega 1996;Katz et al 2003;Tootle et al 2005;Hurrell and Deser 2009). Maxwell et al (2012) identified the NAO as the only significant variable affecting the likelihood of a TCDB impacting the southeast ACS during the period 1950-2008.…”
Section: A Interdecadal Tc Landfall and Tc Precipitation Variabilitymentioning
confidence: 99%
“…These large-scale indices are not intended to capture the natural chaotic component of weather but have been shown to characterize the offshore marine atmosphere, which in the western US drives the seasonal onshore weather patterns. Past research has shown that certain large-scale climate variables have a significant relationship to western US hydrology (Mantua et al, 1997;McCabe and Dettinger, 2002;Beebee and Manga, 2004;Gedalof et al, 2004;Grantz et al, 2005;Tootle et al, 2005;Bonsal et al, 2006;Kingston et al, 2006;Kingston et al, 2007).…”
Section: Seasonal Streamflow Prediction Modelsmentioning
confidence: 99%
“…Other studies have looked at the relationship between large-scale climate teleconnections and weather or hydrologic phenomena (e.g. Mantua et al, 1997;McCabe and Dettinger, 2002;Beebee and Manga, 2004;Gedalof et al, 2004;Grantz et al, 2005;Tootle et al, 2005;Bonsal et al, 2006;Kingston et al, 2006Kingston et al, , 2007, but these have either not explicitly studied the Klamath Basin, or those that have considered the region have not found a related teleconnection index. In the present study, a teleconnection index related to the hydrology of the Klamath Basin has been found and incorporated into statistical streamflow forecasting models.…”
Section: Introductionmentioning
confidence: 99%
“…Krakauer and Fung, 2008;Small et al, 2006;Tootle and Piechota, 2006] and large scale atmospheric circulation patterns [e.g. Barlow et al, 2001;Rajagopalan et al, 2000;Tootle and Piechota, 2006;Tootle et al, 2005].…”
Section: Principles Of Large-scale Hydrological Modellingmentioning
confidence: 99%